Kepemimpinan Pendidikan Dalam Perspektif 6 Sistem Nilai Prof. Dr. Ahmad Sanusi - Muhammad Shofi Mubarak (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: Leadership is a fundamental problem in the progress of society or organization, including school institution. Many theories or concepts proposed by experts, but it is not always suitable for every situation. Therefore, it is necessary to study many aspect of leadership and values. Reseaarchers evaluated the 6 values could be a concerstone of a strong, comprehensive and meaningful for the system 6 could be a cornerstone of a strong, comprehensive and meaningful for the principal to carry out this duties. Can achieve the goal of education leadership, both personal or social, formal or informal, structural or non-structural word or the hereafter.